Pengendalian Persediaan Pakan Ayam Broiler dengan Kendala Kapasitas Gudang pada CV Mitra Utama - Alvin Gautama Tandean; Teguh Oktiarso (Teknik Industri Universitas Ma Chung, 2021)
CV. Mitra Utama is a poultry farming company that provides raw materials to meet the community's demand for broiler chicken meat. However, the availability of chicken feed greatly affects their production process. They often face inventory control problems due to varying feed availability and capacity constraints when ordering. This study aimed to support chicken feed ordering scheduling, plan feed purchasing to achieve optimal results, and determine optimal total feed inventory to minimize total feed inventory costs. The EOQ Multi-Item method was used to control demand or ordering several types of products optimally with the lowest possible total cost. The study results showed the optimal order quantity for each type of chicken feed, and the required storage space for optimal orders. This information is necessary for the company to control feed inventory so that the desired inventory orders achieve optimal results. Food needs are crucial for human survival, and companies in the field of animal husbandry and agriculture play an essential role in providing raw materials to meet these needs. This study provides insights into how a company can optimize their inventory management and ordering process to ensure the availability of chicken feed for their production process.